Analysis of the Effect of Teacher Mutation, Physical Work Environment and Work Motivation on the Performance of Elementary School Teachers in Mentawai Islands Regency: English - Riona, Melani; Koeswara, Hendri; Isfarudi (Pencerah, 2025)
The research, which aims to analyze the effect of teacher mutations, physical work environment, and work motivation on the performance of elementary school teachers in the Mentawai Islands Regency, is motivated by the fact that there are still problems with teacher performance that are influenced by teacher mutations, physical work environment and also work motivation in elementary school teachers in Mentawai Islands Regency. This type of research uses a quantitative approach with multiple linear regression methods—data collection techniques with questionnaires. The respondents of this study were 49 elementary school teachers in the Mentawai Islands District. The sampling method uses the total sampling method, which uses the entire population in this study as the research sample. Hypothesis testing was calculated using the IBM Statistical Package for Social Science (SPSS) version 24.0. The results of this study found that partially and simultaneously, teacher mutations, physical work environment, and work motivation affect the performance of elementary schools in the Mentawai Islands Regency can encourage teachers to try to work better and provide direction and advice to each teacher to continue to be motivated at work so the teachers can work better and increase self-development and improve their performance